Analysis of direct and indirect participation in basketball game actions according to their intensity - Daniel, J. F.; Montagner, P. C.; Padovani, C. R. [UNESP]; Beneli, L. M.; Borin, J. P. (Univ Murcia, 2017)
The purpose of this study was to analyze the intensity of direct (DP) and indirect participation (IP) in basketball game actions. Seven elite male players have participated (28.9 +/- 6.0years, 195.7 +/- 6.7cm, 94.8 +/- 12.4kg, 11.1 +/- 4.9% of body fat), in one official match of the National Basketball League (Brazil). For the match we used a video camera positioned at the highest and central point of the stands and seven HR transmitters Polar Team System, synchronized with the time of a digital stopwatch and later, by video analysis, with the game actions. It was considered DP when the player participated or had moved to participate efectively in the actions; and IP when the player did not participate or had not moved.. It was observed a decrease of more than 5% between DP and IP. he IP in game actions, besides answering certain tactical situations, can also enable greater recovery and ensure high intensity game performance.
Keywords: Training; Performance; Competition